Naturaleza jurídica del consentimiento de bienes jurídico-penales: un análisis a la luz de la Constitución - Chang Kcomt, Romy Alexandra (2015)
The Criminal Code exempts from criminal liabilityany person when they act with valid consent fromthe holder of the legal asset of free disposal. This exclusion of criminal responsibility raises multiplequestions.Which legal rights can be freely disposed? Is it that all individual legal rights are of free disposal? If that is the case, which legal basis justifies it? Does the holder’s consent means that the behavior is unlawful, or is it a non-criminal behavior?In this paper, the author answers all these questions, emphasizing that, according to the type of State we live in, the legal-criminal rights are protected to allow the self-realization of every person. Based on that, the author maintains that all criminal-legal rights are of free disposal, and that  the  holder’s  consent  is  a non-criminality cause.